Investigation of Factors Affecting the Increase in Human Resource Productivity in the Municipality of Jawzjan Province - Intezar, Aburaihan; Noori, Ahmad Zia; Sadiq, Abdul Kabir (Farah Research and Scientific Journal, 2025)
Productivity refers to achieving maximum possible benefits and optimal utilization of human resource’s abilities, talents, and skills to enhance the welfare and comfort of society. The main objective of this research is to investigate the factors affecting the increase in human resource productivity in the municipality of Jawzjan Province. This research is descriptive-analytical in nature, and in terms of data collection, it is field-based (questionnaire) and applied in purpose. To achieve the main objective of the research, 60 questionnaires were distributed among the employees of the municipality of Jawzjan Province. The data were analyzed using the SPSS26 software and the Binomial Test. The significance level of all research hypotheses, according to the Binomial Test output, is less than the 5% error level, meaning that p_ value =.000 < α=.05, indicating the acceptance of the main and sub-hypotheses of the research. Therefore, the results of the research show that employees' job knowledge and skills, their use of information technology, interest in the work environment, and organizational support have a positive and significant impact on increasing their productivity in the municipality of Jawzjan Province.